Taking Stock of Science Standards Implementation: Planning for Progress: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
It has been just over ten years since the release of the Framework on K-12 Science Education and the Next Generation Science Standards. As states continue their implementation efforts of state standards, there is a need for a reflection on these efforts looking at curriculum, instruction, assessment, professional learning, and policy. To identify the conditions and develop a road map for moving implementation efforts forward, the National Academies of Sciences, Engineering, and Medicine held a hybrid summit on April 26 and 27, 2022. Participants shared ideas to imagine what science education could look like in ten years, and how these visions might be achieved. This publication summarizes the presentation and discussion or the event.
Keywords: Education

Promotion, Tenure, and Advancement through the Lens of 2020: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The COVID-19 pandemic upended nearly every aspect of academia, leading colleges and universities to reexamine how they instruct their students and how they reward their faculty. But the pandemic was not the only disruptive event that took place in 2020. Colleges and universities have been forced to address issues related to productivity, teaching,student learning, mentoring, service, and innovative research in the context of remote or hybrid work - all amplified by the increased attention to and discussion of systemic racism, widespread economic hardships, and extreme environmental events. To help leaders of higher education understand how one particular issue - the current faculty reward, advancement, and hiring system - has changed and continues to change in response to several of the events of 2020, the National Academies of Sciences, Engineering, and Medicine commissioned a set of papers. These papers formed the basis for a series of four virtual workshops held on September 20, 23, 27, and 30, 2021. They examined how the events of 2020 have affected existing hiring and advancement policies and practices of institutions of higher education, the differential effects on the promotion and advancement of faculty from different populations, new policies and programs to support faculty, and new approaches that support more equitable faculty advancement. This publication is a short summary of the three workshops on the Next Normal for Leadership and Culture; Recruitment,Retention, and Support; and Advancement of Tenure and Non-Tenure-Track Faculty, as well as the fourth workshop with closing discussions. The presentations were intended to point toward the pandemic and beyond, as well as contextualize how these issues have played out in the last two years.
Keywords: Education

Building Defense Research Capacity at Historically Black Colleges and Universities, Tribal Colleges and Universities, and Minority-Serving Institutions: Proceedings of Three Town Halls - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
A planning committee of the National Academies of Sciences, Engineering, and Medicine convened a series of three hybrid workshops to examine the key issues highlighted in the National Academies 2022 consensus study report, Defense Research Capacity at Historically Black Colleges and Universities and Other Minority Institutions: Transitioning from Good Intentions to Measurable Outcomes. As Department of Defense and other partners sought to implement the 2022 report recommendations, key questions remained to be explored, particularly related to how to seek ways of building research capacity at minority institutions (MIs) and develop true partnerships between MIs, other institutions of higher education, and federal agencies. The workshops featured commissioned research and literature reviews as well as case studies to illuminate problems, barriers, and approaches to increase research capacity at Historically Black Colleges and Universities.
Keywords: Education

Review of Specialized Degree-Granting Graduate Programs of the Department of Defense in STEM and Management - National Research Council (The National Academies Press, 2014)
The United States military is arguably the most intensely technological, complex enterprise in existence. When compared to the gross domestic products of other countries, the Department of Defense (DoD) budget ranks above all but about 20 nations. If viewed as a company, it would be the largest globally with the most employees. Major investments in weapons systems using advanced technologies provide an advantage over competing systems. Each weapon, platform, vehicle, and person in an operating force is a node in one or more advanced networks that provide the ability to rapidly form a coherent force from a large number of broadly distributed elements. DoD's ability to create and operate forces of this nature demands a competent understanding by its workforce of the composition, acquisition, and employment of its technology-enabled forces. Review of Specialized Degree-Granting Graduate Programs of the Department of Defense in STEM and Management focuses on the graduate science, technology, engineering, mathematics and management (STEM+M) education issues of the Air Force, Navy, and Marines. This report assesses the cost, benefits, and organizational placement of DoD institutions that grant degrees in STEM+M and evaluates alternative ways - for example, civilian institutions and distance learning - to ensure adequate numbers and high-quality education outcomes for DoD personnel.
Keywords: Education

The Relative Risks of School Travel: A National Perspective and Guidance for Local Community Risk Assessment -- Special Report 269 - Transportation Research Board (The National Academies Press, 2002)
TRB Special Report 269 - The Relative Risks of School Travel: A National Perspective and Guidance for Local Community Risk Assessment presents a method to estimate, on a per-mile and per-trip basis, the relative risks that students face in traveling to and from school by walking, bicycling, riding in passenger vehicles with adult drivers, riding in passenger vehicles with teenage drivers, or taking a bus.  These estimated risk measures can assist localities in developing policies to improve the safety of students traveling to school and in evaluating policies that affect mode choices by students and their parents.  The report also includes checklists of actions to reduce the risks associated with each mode of school travel.

STEM Learning Is Everywhere: Summary of a Convocation on Building Learning Systems - National Research Council (The National Academies Press, 2014)
Science, technology, engineering, and mathematics (STEM) permeate the modern world. The jobs people do, the foods they eat, the vehicles in which they travel, the information they receive, the medicines they take, and many other facets of modern life are constantly changing as STEM knowledge steadily accumulates. Yet STEM education in the United States, despite the importance of these subjects, is consistently falling short. Many students are not graduating from high school with the knowledge and capacities they will need to pursue STEM careers or understand STEM-related issues in the workforce or in their roles as citizens. For decades, efforts to improve STEM education have focused largely on the formal education system. Learning standards for STEM subjects have been developed, teachers have participated in STEM-related professional development, and assessments of various kinds have sought to measure STEM learning. But students do not learn about STEM subjects just in school. Much STEM learning occurs out of school—in organized activities such as afterschool and summer programs, in institutions such as museums and zoos, from the things students watch or read on television and online, and during interactions with peers, parents, mentors, and role models. To explore how connections among the formal education system, afterschool programs, and the informal education sector could improve STEM learning, a committee of experts from these communities and under the auspices of the Teacher Advisory Council of the National Research Council, in association with the California Teacher Advisory Council organized a convocation that was held in February 2014. Entitled "STEM Learning Is Everywhere: Engaging Schools and Empowering Teachers to Integrate Formal, Informal, and Afterschool Education to Enhance Teaching and Learning in Grades K-8," the convocation brought together more than 100 representatives of all three sectors, along with researchers, policy makers, advocates, and others, to explore a topic that could have far-reaching implications for how students learn about STEM subjects and how educational activities are organized and interact. This report is the summary of that meeting. STEM Learning is Everywhere explores how engaging representatives from the formal, afterschool, and informal education sectors in California and from across the United States could foster more seamless learning of STEM subjects for students in the elementary and middle grades. The report also discusses opportunities for STEM that may result from the new expectations of the Next Generation Science Standards and the Common Core Standards for Mathematics and Language Arts.
Keywords: Education

Prospectus for National Knowledge Assessment (The National Academies Press, 1996)

Building a Better NASA Workforce: Meeting the Workforce Needs for the National Vision for Space Exploration - National Research Council (The National Academies Press, 2007)
The Vision for Space Exploration (VSE) announced by President George W. Bush in 2004 sets NASA and the nation on a bold path to return to the Moon and one day put a human on Mars. The long-term endeavor represented by the VSE is, however, subject to the constraints imposed by annual funding. Given that the VSE may take tens of years to implement, a significant issue is whether NASA and the United States will have the workforce needed to achieve that vision. The issues range from short-term concerns about the current workforce's skills for overseeing the development of new spacecraft and launch vehicles for the VSE to long-term issues regarding the training, recruiting, and retaining of scientists and engineers in-house as well as in industry and academia. Asked to explore science and technology (S&T) workforce needs to achieve the nation's long-term space exploration, the Committee on Meeting the Workforce Needs for the National Vision for Space Exploration concluded that in the short term, NASA does not possess the requisite in-house personnel with the experience in human spaceflight systems development needed to implement the VSE. But the committee acknowledges that NASA is cognizant of this fact and has taken steps to correct it, primarily by seeking to recruit highly skilled personnel from outside NASA, including persons from industry and retirees. For the long term, NASA has to ask if it is attracting and developing the talent it will need to execute a mission to return to the Moon, and the agency must identify what it needs to do to attract and develop a world-class workforce to explore other worlds. A major challenge for NASA is reorienting its human spaceflight workforce from the operation of current vehicles to the development of new vehicles at least throughout the next decade, as well as starting operations with new rockets and new spacecraft. The committee emphasizes further that when evaluating its future workforce requirements, NASA has to consider not only programs for students, but also training opportunities for its current employees. NASA's training programs at the agency's various field centers, which are focused on NASA's civil service talent, require support to prevent the agency's internal skill base from withering. Furthermore, NASA faces the risk that, if it fails to nurture its own internal workforce, skilled personnel will be attracted to other government agencies and industry. Building a Better NASA Workforce: Meeting the Workforce Needs for the National Vision for Space Exploration explains the findings and recommendations of the committee.
Keywords: Space and Aeronautics; Education

State of School Science: A Review of the Teaching of Mathematics, Science and Social Studies in American Schools, and Recommendations for Improvements. - National Research Council (The National Academies Press, 1979)
Keywords: Education

Undergraduate Education in the Sciences for Students in Agriculture and Natural Resources: Summary of Proceedings of Regional Conferences (The National Academies Press, 1971)
Keywords: Education

The Funding of Social Knowledge Production and Application: A Survey of Federal Agencies - National Research Council (The National Academies Press, 1978)
Keywords: Education

Early Experience and Visual Information Processing in Perceptual and Reading Disorders: Proceedings of a Conference Held October 27-30, 1968, at Lake Mohonk, New York, in Association With the Committee on Brain Sciences, Division of Medical Sciences, National Research Council. Edited - National Research Council (The National Academies Press, 1970)
Keywords: Education

Envisioning the Data Science Discipline: The Undergraduate Perspective: Interim Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The need to manage, analyze, and extract knowledge from data is pervasive across industry, government, and academia. Scientists, engineers, and executives routinely encounter enormous volumes of data, and new techniques and tools are emerging to create knowledge out of these data, some of them capable of working with real-time streams of data. The nation’s ability to make use of these data depends on the availability of an educated workforce with necessary expertise. With these new capabilities have come novel ethical challenges regarding the effectiveness and appropriateness of broad applications of data analyses.
Keywords: Education; Math, Chemistry, and Physics; Computers and Information Technology; Surveys and Statistics

Evaluation of the Voluntary National Tests: Phase 1 - National Research Council (The National Academies Press, 1999)
In his 1997 State of the Union address, President Clinton announced a federal initiative to develop tests of 4th-grade reading and 8th-grade mathematics that would provide reliable information about student performance at two key points in their educational careers. According to the U.S. Department of Education, the Voluntary National Tests (VNT) would create a catalyst for continued school improvement by focusing parental and community-wide attention on achievement and would become new tools to hold school systems accountable for their students' performance. The National Assessment Governing Board (NAGB) has responsibility for development of the VNT. Congress recognized that a testing program of the scale and magnitude of the VNT initiative raises many important technical questions and requires quality control throughout development and implementation. In P.L. 105-78, Congress called on the National Research Council (NRC) to evaluate a series of technical issues pertaining to the validity of test items, the validity of proposed links between the VNT and the National Assessment of Educational Progress (NAEP), plans for the accommodation and inclusion of students with disabilities and English-language learners, plans for reporting test information to parents and the public, and potential uses of the tests. This report covers phase 1 of the evaluation (November 1997-July 1998) and focuses on three principal issues: test specifications and frameworks; preliminary evidence of the quality of test items; and plans for the pilot and field test studies, for inclusion and accommodation, and for reporting VNT results.
Keywords: Education

Enhancing Professional Development for Teachers: Potential Uses of Information Technology: Report of a Workshop - National Research Council (The National Academies Press, 2007)
Teachers, like other professionals, need to stay informed about new knowledge and technologies. Yet many express dissatisfaction with the professional development opportunities made available to them in schools and insist that the most effective development programs they have experienced have been self-initiated. Enhancing Professional Development for Teachers explores how the provision of professional development through online media has had a significant influence on the professional lives of an increasing number of teachers. Growing numbers of educators contend that online teacher professional development (OTPD) has the potential to enhance and even transform teachers' effectiveness in their classrooms and over the course of their careers. They also acknowledge that it raises many challenging questions regarding costs, equity, access to technology, quality of materials, and other issues. Enhancing Professional Development for Teachers suggests that teachers be active participants in planning and implementation of any new technologies that enhance professional development. The book recommends that federal and state policy makers take on the responsibility of promoting equal access to technology while the federal government and foundations play an important role by supporting the development, evaluation, and revision of OTPD.
Keywords: Education

Transforming Research and Higher Education Institutions in the Next 75 Years: Proceedings of the 2022 Endless Frontier Symposium - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
On September 22, 2022, the National Academy of Sciences held a symposium entitled Endless Frontier 2022: Research and Higher Education Institutions for the Next 75 Years. The event was a follow up to a February 2020 NAS symposium convened to celebrate the 75th anniversary of the landmark report Science, the Endless Frontier. Building on the 2020 symposium and on lessons learned during the COVID-19 pandemic, the September 2022 symposium sought to generate tools, strategies, and actionable steps that people and institutions can implement to ensure that science and technology continue to serve the public good. The symposium was designed to progress from broad perspectives that encompass the entire science and technology enterprise to consideration of more specific issues. This proceedings summarizes the 2022 symposium.
Keywords: Education

Evaluation of the Voluntary National Tests, Year 2: Interim Report (The National Academies Press, 1999)
Keywords: Education

Learning to Think Spatially - National Research Council (The National Academies Press, 2006)
Learning to Think Spatially examines how spatial thinking might be incorporated into existing standards-based instruction across the school curriculum. Spatial thinking must be recognized as a fundamental part of K–12 education and as an integrator and a facilitator for problem solving across the curriculum. With advances in computing technologies and the increasing availability of geospatial data, spatial thinking will play a significant role in the information-based economy of the twenty-first century. Using appropriately designed support systems tailored to the K–12 context, spatial thinking can be taught formally to all students. A geographic information system (GIS) offers one example of a high-technology support system that can enable students and teachers to practice and apply spatial thinking in many areas of the curriculum.
Keywords: Education

Evaluation of the Voluntary National Tests, Year 2: Final Report - National Research Council (The National Academies Press, 1999)
In his 1997 State of the Union address, President Clinton announced a federal initiative to develop tests of 4th-grade reading and 8th-grade mathematics that could be administered on a voluntary basis by states and school districts beginning in spring 1999. The principal purpose of the Voluntary National Tests (VNT) is to provide parents and teachers with systematic and reliable information about the verbal and quantitative skills that students have achieved at two key points in their educational careers. The U.S. Department of Education anticipated that this information would serve as a catalyst for continued school improvement, by focusing parental and community attention on achievement and by providing an additional tool to hold school systems accountable for their students' performance in relation to nationwide standards. Shortly after initial development work on the VNT, Congress transferred responsibility for VNT policies, direction, and guidelines from the department to the National Assessment Governing Board (NAGB, the governing body for the National Assessment of Educational Progress). Test development activities were to continue, but Congress prohibited pilot and field testing and operational use of the VNT pending further consideration. At the same time, Congress called on the National Research Council (NRC) to assess the VNT development activities. Since the evaluation began, the NRC has issued three reports on VNT development: an interim and final report on the first year's work and an interim report earlier on this second year's work. This final report includes the findings and recommendations from the interim report, modified by new information and analysis, and presents our overall conclusions and recommendations regarding the VNT.
Keywords: Education

Approaches to the Evaluation of Sexual Harassment Prevention and Response Efforts - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Evaluation, an important component of all research, is critical to integrate into interventions addressing sexual harassment, because the targets of such harassment can suffer serious consequences, including physical and emotional harm, lost educational opportunities, and negative effects on their career. Not only are the consequences potentially severe, but the problem is pervasive across all levels of academia. Studies show that 20–50 percent of undergraduate and graduate students experience sexual harassment from faculty or staff, as well as nearly 50 percent of women faculty and staff in academia. Moreover, despite efforts in recent decades to prevent and respond effectively to sexual harassment, it remains a significant issue with no clear decline in incidence rates. This paper offers insight into selecting the appropriate methods for evaluating interventions based on evidence, case studies, and the perspectives and experiences of the authors. The goal of the paper is to provide interested parties in higher education with an introduction to methods and approaches to evaluating interventions designed to prevent and respond to sexual harassment in their institutions. This individually-authored issue paper was created by members of the Evaluation Working Group of the Action Collaborative on Preventing Sexual Harassment in Higher Education to explore the challenges and research areas related to the evaluation of a wide range of efforts to address sexual harassment, which they present in this document. The Action Collaborative on Preventing Sexual Harassment in Higher Education of the National Academies of Sciences, Engineering, and Medicine brings together academic and research institutions and key stakeholders to work toward targeted, collective action on addressing and preventing sexual harassment across all disciplines and among all people in higher education. The Action Collaborative includes four working groups (Prevention, Response, Remediation, and Evaluation) that identify topics in need of research, gather information, and publish resources for the higher education community.
Keywords: Education